Innovation ecosystems and short chains in healthy food supply to vulnerable populations in Mato Grosso do Sul during the Covid-19 pandemic - Pitaluga, Christiane; Alexandre Le Bourlegat , Cleonice (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2021)
Inserted in this context of the pandemic caused by Covid-19 and food insecurity, it has been important to reflect on the rethinking of “new forms” of territorialized commercialization, distribution and consumption, which may involve the participation of communities, in the search for quick and more agile solutions. The objective of the study was to verify the conditions in which two innovation ecosystems were structured and operated in Mato Grosso do Sul, which emerged at the encouragement of the Banco do Brasil Foundation during the Covid-19 pandemic, working through short chains, in the search for urgent solutions to supply healthy food to the most vulnerable populations. The object of this investigation was the ecosystems articulated by the Central dos Trabalhadores/as da Economia Solidáriain Campo Grande and the Associação dos Produtores Orgânicos de Mato Grosso do Sul (APOMS) in Glória de Dourados, with an area of activity in several surrounding municipalities, involving suppliers and the beneficiary population. The research, of a descriptive and exploratory type, was based on an initial bibliographic review, followed by the collection of information from bibliographic and documentary sources and also the application of semi-structured interviews to those responsible for the entities that articulate each ecosystem. It was possible to verify that the structure and functioning of the two innovation ecosystems responded in great part, not only to the context of the circumstances and territories in which they were manifested, but also to the nature of public incentive policies. In addition to boosting the local economy, they favored the social inclusion of vulnerable populations and, even if in a palliative way, they guaranteed food security for numerous families in the territories where they demonstrated an innovative way of building social markets in Mato Grosso do Sul.